A rare case report of oral prednisolone dependence in a middle aged man - A., Chamelee; L., Lavanya; D., Vijayanand; S., Chandraleka G. (International Journal of Research in Medical Sciences, 2019)
Dependence is an uncommon, but potentially sinister complication of corticosteroid therapy. prednisolone was the most frequently implicated corticosteroid in steroid dependence. Here we report a rare case of oral prednisolone dependence in middle aged man who had chronic asthma.